1995
DOI: 10.1017/s0022215100132050
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of head and neck cancer with photodynamic therapy: results after one year

Abstract: Photodynamic therapy (PDT) is a new and promising treatment modality for the treatment of malignant disease. This paper reports the preliminary experience of our group in the use of this therapy for the treatment of tumours arising in the head and neck. The majority of treatments in these cases have used a second generation systemic photosensitizer, weto-tetrahydroxyphenylchlorin (ra-THPC). Two other cases were treated with either Photofrin 2 (a first generation systemic sensitizer) or with the topical photose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 8 publications
(1 reference statement)
0
21
0
Order By: Relevance
“…Early clinical work using PDT on the tumor bed after resection of mesotheliomas showed that a dose of 0.3 mg/kg body weight mTHPC, activated with red light at 650 nm with a dose of 10J/cm 2 , produced 10-mm depth of tumor necrosis (Ris et al, 1991) with safe healing. The use of this photosensitizer to treat a variety of tumors in the head and neck region has been reported in a diverse group of 11 patients (Dilkes et al, 1995) with encouraging results.…”
mentioning
confidence: 99%
“…Early clinical work using PDT on the tumor bed after resection of mesotheliomas showed that a dose of 0.3 mg/kg body weight mTHPC, activated with red light at 650 nm with a dose of 10J/cm 2 , produced 10-mm depth of tumor necrosis (Ris et al, 1991) with safe healing. The use of this photosensitizer to treat a variety of tumors in the head and neck region has been reported in a diverse group of 11 patients (Dilkes et al, 1995) with encouraging results.…”
mentioning
confidence: 99%
“…Exogenous 6-aminolaevulinic acid (ALA) is becoming widely used as an inducer of endogenous synthesis of protoporphyrin IX (PPIX), a photosensitizer used in photodynamic therapy (PDT) (Dilkes et al, 1995;Leveckis et al, 1995;Chang et al, 1996;Fromm et al, 1996). One of the limitations of this technique may be the extent to which ALA can enter the cell.…”
mentioning
confidence: 99%
“…Extensive radiotherapy may cause mucositis, xerostomia, loss of taste and smell and even osteoradionecrosis. Surgical excision may leave patients with aesthetic and functional disabilities, impairing swallowing and speaking [27].…”
Section: Cancer Therapymentioning
confidence: 99%